2012
DOI: 10.1098/rspb.2012.1609
|View full text |Cite
|
Sign up to set email alerts
|

Sexual dichromatism in frogs: natural selection, sexual selection and unexpected diversity

Abstract: Sexual dichromatism, a form of sexual dimorphism in which males and females differ in colour, is widespread in animals but has been predominantly studied in birds, fishes and butterflies. Moreover, although there are several proposed evolutionary mechanisms for sexual dichromatism in vertebrates, few studies have examined this phenomenon outside the context of sexual selection. Here, we describe unexpectedly high diversity of sexual dichromatism in frogs and create a comparative framework to guide future analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
118
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(123 citation statements)
references
References 59 publications
3
118
1
Order By: Relevance
“…Bell and Zamudio, 2012;Doucet and Mennill, 2010;Maan and Cummings, 2009;Ries et al, 2008). Sexual dichromatism is relatively rare in anurans, having been documented in only 2% of species (Bell and Zamudio, 2012). Bell and Zamudio (2012) distinguish two classes of sexual dichromatism in anurans: ontogenetic dichromatism and dynamic dichromatism.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Bell and Zamudio, 2012;Doucet and Mennill, 2010;Maan and Cummings, 2009;Ries et al, 2008). Sexual dichromatism is relatively rare in anurans, having been documented in only 2% of species (Bell and Zamudio, 2012). Bell and Zamudio (2012) distinguish two classes of sexual dichromatism in anurans: ontogenetic dichromatism and dynamic dichromatism.…”
Section: Introductionmentioning
confidence: 97%
“…Sexual dichromatism has recently garnered attention in anurans (e.g. Bell and Zamudio, 2012;Doucet and Mennill, 2010;Maan and Cummings, 2009;Ries et al, 2008). Sexual dichromatism is relatively rare in anurans, having been documented in only 2% of species (Bell and Zamudio, 2012).…”
Section: Introductionmentioning
confidence: 98%
“…Dynamic sexual dichromatism is a temporary colour change that occurs in male frogs during the breeding period (Bell and Zamudio 2012). This phenomenon has been recorded in the stream-breeding hylids Litoria jungguy, L. lesueuri, L. wilcoxi (Donnellan & Mahony 2004;Kriger & Hero 2007) and L. revelata (Webster 2013).…”
Section: Discussionmentioning
confidence: 99%
“…al. 2012); or the bright colour being evidence of the fitness of the male frog (Bell and Zamudio 2012). L. jervisiensis closely resembles L. revelata and some authors have placed these frogs in a distinct species-group (Barker et.…”
Section: Discussionmentioning
confidence: 99%
“…Sexual dichromatism is frequent between species of birds (Bortolotti et al 1996;Dale et al 2015), amphibians (Bell and Zamudio 2012) and fish (Kodric-Brown 1998). Human skin color, apart from being an important indicator of current health (Fink et al 2012;Re et al 2011;Stephen et al 2009b;Whitehead et al 2012), has been shown to be different between human females and males (Van den Berghe and Frost 1986) but also to be considered attractive in mate preferences (Carrito et al 2016).…”
Section: Introductionmentioning
confidence: 99%